2020
DOI: 10.1017/ice.2020.1299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the negative predictive value of methicillin-resistant Staphylococcus aureus nasal swab screening in patients with acute myeloid leukemia

Abstract: Objective: Methicillin-resistant Staphylococcus aureus (MRSA) nasal swabs are utilized to guide the discontinuation of empiric MRSA therapy. In multiple studies, MRSA nasal swabs have been shown to have a negative predictive value (NPV) of ~99% in non-oncology patients with pneumonia and other infections. We evaluated the performance characteristics of a negative MRSA nasal swab in the acute myeloid leukemia (AML) populaion to determine its NPV. Design: Retrospective chart review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“… 50 , 51 Neutropenic patients have generally not been well represented in these studies, but there are now three published studies evaluating the predictive value of PCR-based MRSA nasal carriage assessment and MRSA infection in neutropenic patients. 52 54 All three studies found a low prevalence of MRSA colonization and infection. The MRSA PCR demonstrated a negative predictive value of 97.5% to 99%, consistent with studies in non-neutropenic patients.…”
Section: Updates In Diagnosismentioning
confidence: 95%
See 2 more Smart Citations
“… 50 , 51 Neutropenic patients have generally not been well represented in these studies, but there are now three published studies evaluating the predictive value of PCR-based MRSA nasal carriage assessment and MRSA infection in neutropenic patients. 52 54 All three studies found a low prevalence of MRSA colonization and infection. The MRSA PCR demonstrated a negative predictive value of 97.5% to 99%, consistent with studies in non-neutropenic patients.…”
Section: Updates In Diagnosismentioning
confidence: 95%
“…Emerging data support the utilization of MRSA screening to aid in de-escalation of vancomycin therapy and clinicians should work to incorporate them into clinical protocols and practice, particularly if local prevalence of MRSA infection is low. 52 54 …”
Section: Updates In Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the critical concerns associated with importation and nosocomial infection cases, identifying them rapidly and accurately still remains a challenging problem. Current methods to identify them include surveillance tests 13,14 , machine learning-based methods 15,16 , and transmission modeling-based methods [17][18][19][20][21][22][23] . However, they all suffer from unavoidable drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…This has allowed for the confident de-escalation and avoidance of empiric anti-MRSA treatment before the finalization of cultures [ 3 , 4 ]. However, MRSA nares screening is not well validated in high-risk individuals, including those with neutropenia, hematopoietic stem cell transplant (HSCT) recipients, and solid organ transplant (SOT) recipients [ 5 , 6 ].…”
mentioning
confidence: 99%